The Building Database System Ornamental Fish Supply Chain For Exporting - Wonginyu, Kanokphat; Sukcharoenpong, Sompon; Dithasathorncharoen, Santi (Journal of Management Science Nakhon Pathom Rajabhat University, 2018)
The lack of data management on ornamental fishes supply chain for export from up-stream to down-stream effected to related agents. It was about as it needed to make decision for the related agents. Private sectors required the data before their decision – making for business, as well as the administrators needed the data for making policy. The lack of the data management caused of competitive capabilities in ornamental fishes industry in Thailand resulted in less capability than competitors in international market. The data management on the ornamental fish supply chain for export could be done by collect all data on productive processes, suppliers, producers, consolidators or wholesalers, exporters, logistics service providers, international competitors and all concerned government bureaus. All data then was managed to be database in easily accessing via web page, web board and it should be linked to the network main information. The development of database on ornamental fish supply chain for export found that it should be related agents who responded directly in the process to control, improve and update the data system. This was for increase the capabilities on international marketing competition. The concerned organizations had to check update, inform and cooperate with other related agents for the data development The database on ornamental fishes supply chain for export had been informed at https://msc.npru.ac.th/fish/index.php. The data was last updated in the 30th September 2011 of all 843 lists. Article history : Accepted 15 May 2014 SIMILARITY INDEX = 5.16